The interaction of coenzyme Q with phosphatidylethanolamine membranes - Gómez‐Fernández, Juan C.; Llamas, Maria A.; Aranda, Francisco J. (European journal of biochemistry, 1999)
Coenzyme Q (CoQ) is a component of the mitochondrial respiratory chain which carries out additional membrane functions, such as acting as an antioxidant. The location of CoQ in the membrane and the interaction with the phospholipid bilayer is still a subject of debate. The interaction of CoQ in the oxidized (ubiquinone‐10) and reduced (ubiquinol‐10) state with membrane model systems of 1,2‐dielaidoyl‐sn‐glycero‐3‐phosphoethanolamine (Ela2Gro‐P‐Etn) has been studied by means of differential scanning calorimetry (DSC), 31P‐nuclear magnetic resonance (31P‐NMR) and small angle X‐ray diffraction (SAXD). Ubiquinone‐10 did not visibly affect the lamellar gel to lamellar liquid‐crystalline phase transition of Ela2Gro‐P‐Etn, but it clearly perturbed the multicomponent lamellar liquid‐crystalline to lamellar gel phase transition of the phospholipid. The perturbation of both transitions was more effective in the presence of ubiquinol‐10. A location of CoQ forming head to head aggregates in the center of the Ela2Gro‐P‐Etn bilayer with the polar rings protruding toward the phospholipid acyl chains is suggested. The formation of such aggregates are compatible with the strong hexagonal HII phase promotion ability found for CoQ. This ability was evidenced by the shifting of the lamellar to hexagonal HII phase transition to lower temperatures and by the appearance of the characteristic hexagonal HII31P‐NMR resonance and SAXD pattern at temperatures at which the pure Ela2Gro‐P‐Etn is still organized in extended bilayer structures. The influence of CoQ on the thermotropic properties and phase behavior of Ela2Gro‐P‐Etn is discussed in relation to the role of CoQ in the membrane.